PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BOOKWALL TERHADAP PEMAHAMAN DAN KEMANDIRIAN SISWA - Anik Alfiana; Yunita Hariyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted to determine whether there is an effect of using Bookwall learning media on students’ understanding and learning independence at UPTD SDN Burneh 1 Bangkalan in IPAS (Science and Social Studies) learning. The research employed a quantitative approach with a one-group pretest–posttest design. The population of this study consisted of all students in class 3A, totaling 30 students, and the entire population was used as the research sample. The instruments used in this study were test questions to measure students’ understanding and questionnaires to assess their learning independence. Several data analysis tests were conducted, including a validity test to determine the validity of the research instruments, a reliability test to measure the consistency of valid instruments, and a normality test to examine whether the data were normally distributed. Furthermore, a paired sample t-test was used to identify the difference in mean scores between two related variables derived from the same sample. All statistical analyses were performed using SPSS software. The results of the study indicate that the use of Bookwall learning media in IPAS learning has a significant effect on students’ understanding and learning independence. This is evidenced by the significance value of 0.000, which is less than 0.05 (0.000 < 0.05). Therefore, it can be concluded that there is a statistically significant difference between the pretest and posttest results after the implementation of the Bookwall learning media.